Integrating Sustainable Development Goals (SDGs) into Human Resource Management: A Systematic Review, Critical Appraisal, and Framework for the Logistics and Transportation Sector - Darwisman, Samuel; Simanjuntak, Yosef Ricky; Sihombing, Sarinah; Setyawati, Aswanti (Dinasti Review, 2025)
The logistics and transportation sector faces pressure to align with the Sustainable Development Goals (SDGs), yet the role of Human Resource Management (HRM) lacks a synthesized, critically appraised evidence base. This study closes this gap via a systematic literature review guided by PRISMA 2020. Searching major databases yielded 25 high-impact review articles (2019-2025), which were critically appraised using the CASP checklist. Thematic analysis identified five core determinants for successful integration: Technological Adoption, Circular Economy Principles, Coherent Policy Frameworks, Workforce Awareness, and Sustainable Resource Management. Based on these findings, we propose an integrative socio-technical framework. This study provides a validated, evidence-based roadmap for stakeholders to develop resilient and sustainable HRM strategies, moving beyond a simple literature summary to offer a critically validated foundation for the industry.